Pharmacoperone Identification for Therapeutic Rescue of Misfolded Mutant Proteins - Conn, P Michael; Janovick, Jo Ann (Frontiers in Endocrinology, 2011)
G protein-coupled receptors (GPCRs), which includes the gonadotropin releasing hormone (GnRH) receptor (GnRHR), comprises the largest family of validated drug targets—more than half of all approved drugs derive their benefits by selective targeting of GPCRs. Most drugs in this class are either agonists or antagonists of GPCRs and high throughput screens (HTSs) have typically been designed and performed with a view toward identification of such compounds as lead drug candidates. This manuscript presents the case that valuable drugs which effect the trafficking of GPCRs may have been overlooked because pharmacoperones have been selected from existing screens that identify agonists and antagonists. A “gain of activity assay” is proposed; this assay relies on the expression of a mutant of the GnRHR that is known to be rescuable by pharmacoperone drugs, and which is restored to activity in their presence. Accordingly, “hits” are identified by the appearance of activity. The gene for the mutant is under control of tetracycline and may be prevented from being expressed. This is a valuable feature since it allows false positives to be identified. Such drugs will show apparent activity whether or not the mutant is expressed. This assay will enable identification of these drugs from chemical libraries and does not rely on their activity as agonists or antagonists.